Trade patterns in Argentina, Chile and Peru. - Chan, Mee Yee. (2008)
As the new millennium approaches, the three major global trading regions are North America, the European Union (EU) and Asia. Except for Mexico, not much attention has been paid to Latin America, not to mention South America. Brazil is the most active trading country in terms of exports and imports in South America, followed by Argentina, Chile and Peru. With the formation of several major trade blocs, such as the North America Free Trade Agreement (NAFTA), the EU and the Asia Pacific Economic Co-operation (APEC), the South American region is becoming very attractive. Hence, trade patterns in Argentina, Chile and Peru should not be overlooked.